Evaporation Ripped Metallurgical Pore in Electron Beam Freeform Fabrication of Ti-6-Al-4-V. Issue 15 (17th November 2016) - Chen, Tao; Pang, Shengyong; Tang, Qun; Suo, Hongbo; Gong, Shuili
Abstract : A rare metallurgical pore, which has near-spherical contour with ripped inner surface characteristics, is found in Ti-6-Al-4-V deposits during vacuum electron beam freeform fabrication. The pores are characterized with scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS) in the experiments. The EDS results indicate the mass fraction of Al element reduces to 3.8% on the inner surface of the pore due to evaporation loss. It is shown that the formation of the ripped surface profile of this metallurgical pore is attributed to a particular evaporation process, in which the volatile elements (most likely Al) evaporate in the mush zone of Ti-6-V-4-V alloy during solidification under vacuum. The necessary pressure and temperature conditions of this particular evaporation are theoretically deduced. It is found that the ambient pressure around the metallurgical bubbles in the mush zone should be lower than the pressure at the triple point in the phase diagram of the volatile element (Al or Ti). Moreover, the temperature around the bubbles should be greater than the boiling point of the volatile element (Al or Ti), but smaller than the liquidus temperature of Ti-6-Al-4-V alloy under vacuum.